Assessing Degree of maternal separation anxiety in working women who put their first child to kindergartens of Universities of Medical Sciences in Tehran, 1994 - Rouhani, K (Iran University of Medical Sciences, 1995)
This field study was conducted on 60 women who working in related centers of Universities of Medical Sciences in Tehran. Data gathering tool was maternal separation anxiety questionnaire that designated by Hock & et al. (1982).  Findings revealed that majority of the research units (71.7%), have high degree of maternal separation anxiety. Mean degree of maternal separation anxiety was (21.22±3.19). Chi-square test showed that there are significant relationship between some personal and familial characteristics and degree of maternal separation anxiety. Also, this significant relationship was between some personal and familial characteristics and mother's perceptions factors about effects of child separation, and mother's worries about her job.